Investigating the Mediating Role of Self-Compassion in the Relationship between Spiritual Intelligence and Hope in Female Nurses of Neyshabur-Iran Hospitals in 2019 - Samaneh Fakhrian; Mustafa Bolghan-Abadi (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Nurses are among the individuals who are under various forms of stress and physical and psychological harm due to the nature of their occupation. Objectives: The present study aimed to investigate the mediating role of self-compassion in the relationship between spiritual intelligence and hope in female nurses. Methods: The method of the current research was descriptive-correlational. In this research, 183 female nurses of Neyshabur hospitals were selected by convenience sampling method in 2019. Participants completed King's Spiritual Intelligence Questionnaire (2008), Snyder's Hope Questionnaire (2000), and Neff's Self-Compassion Scale (2003). The data were analyzed using SPSS software version 24, descriptive statistics (mean, standard deviation, frequency, and frequency percentage), path analysis method, and Pearson correlation coefficient. Results: The mean (SD) age of participants was 35.22(5.91) years. Spiritual intelligence and self-compassion were predictors of hope in female nurses (p<0.005). Overall, the results showed that self-compassion had a mediating role in the relationship between spiritual intelligence and hope in female nurses (p<0.05). Conclusion: According to the findings, it seems that individuals who have high spiritual intelligence feel self-compassion and therefore are more hopeful.